Assessing coronary artery stenosis exacerbated impact on left ventricular function and deformation in metabolic syndrome patients by 3.0 T cardiac magnetic resonance imaging - Yi-Ning Jiang; Yue Gao; Chen-Yan Min; Ying‑Kun Guo; Rong Xu; Li-Ting Shen; Wen-lei Qian; Yuan Li; Zhi-Gang Yang (Cardiovascular Diabetology)
Abstract Background Metabolic syndrome (MetS) and coronary artery stenosis (CAS) independently increase the risk of cardiovascular events, while the impact of CAS on left ventricular (LV) function and deformation in MetS patients remains unclear. This study investigates how varying degrees of CAS exacerbate LV function and myocardial deformation in MetS patients. Methods One hundred thirty-one MetS patients who underwent CMR examinations were divided into two groups: the MetS(CAS−) group (n = 47) and the MetS(CAS+) group (n = 84). The MetS(CAS+) group was divided into MetS with non-obstructive CAS(NOCAS+) (n = 30) and MetS with obstructive CAS(OCAS+) group (n = 54). Additionally, 48 age- and sex-matched subjects were included as a control group. LV functional and deformation parameters were measured and compared among subgroups. The determinants of decreased LV global peak strains in all MetS patients were identified using linear regression. The receiver operating characteristic (ROC) curve and logistic regression model (LRM) evaluated the diagnostic accuracy of the degree of CAS for identifying impaired LV strain. Results Compared to MetS(CAS−), MetS(NOCAS+) showed a significantly increased LV mass index (p < 0.05). Global longitudinal peak strain was decreased gradually from MetS(CAS−) through MetS(NOCAS+) to MetS(OCAS+) (− 13.02 ± 2.32% vs. − 10.34 ± 4.05% vs. − 7.55 ± 4.48%, p < 0.05). MetS(OCAS+) groups showed significantly decreased LV global peak strain (GPS), PSSR and PDSR in radial and circumferential directions compared with MetS(NOCAS+) (all p < 0.05). The degree of CAS was independently associated with impaired global radial peak strain (GRPS) (β =  − 0.289, p < 0.001) and global longitudinal peak strain (GLPS) (β = 0.254, p = 0.004) in MetS patients. The ROC analysis showed that the degree of CAS can predict impaired GRPS (AUC = 0.730) and impaired GLPS (AUC = 0.685). Conclusion Besides traditional biochemical indicators, incorporating CAS assessment and CMR assessment of the LV into routine evaluations ensures a more holistic approach to managing MetS patients. Timely intervention of CAS is crucial for improving cardiovascular outcomes in this high-risk population.